Association Between Severe Vitamin D Deficiency, Lung Function and Asthma Control [Asociación del déficit grave de vitamina D con la función pulmonar y el control del asma] - (:unkn) unknown (Elsevier Doyma, 2017)
Introduction To examine the relationship between severe vitamin D deficiency, asthma control, and pulmonary function in Turkish adults with asthma. Methods One hundred six asthmatic patients underwent pulmonary function tests skin prick test, peripheral blood eosinophil counts, IgE, body mass index and vitamin D levels were determined. Patients were divided into 2 subgroups according to vitamin D levels (vitamin D level < 10 ng/ml and vitamin D level ≥ 10  ng/ml). Asthma control tests were performed. Results The mean age of subgroup I (vitamin D level < 10) was 37 ± 10 and the mean age of subgroup II (vitamin D level ≥ 10 ng/ml) was 34 ± 8. Sixty-six percent of patients had severe vitamin D deficiency (vitamin D level < 10 ng/ml). There was a significant trend towards lower absolute FEV1 (L) values in patients with lower vitamin D levels (P = .001). Asthma control test scores were significantly low in the severe deficiency group than the other group (P = .02). There were a greater number of patients with uncontrolled asthma (asthma control test scores < 20) in the severe vitamin D deficiency group (P = .040). Patients with severe vitamin D deficiency had a higher usage of inhaled corticosteroids than the group without severe vitamin D deficiency (P = .015). There was a significant trend towards lower absolute FEV1 (L) (P = .005, r = .272) values in patients with lower vitamin D levels. Vitamin D levels were inversely related with body mass index (P = .046). Conclusion The incidence of severe vitamin D deficiency was high in adult Turkish asthmatics. In addition, lower vitamin D levels were associated with poor asthma control and decreased pulmonary function. © 2016 SEPAR
Keywords: Asthma control; FEV1; Pulmonary function; Severe vitamin D deficiency